A representação midiática de pessoas vivendo com HIV: proposta de guia para cobertura jornalística - VASCONCELOS, Ismael Conceição (2025)
The present work consists of an applied research with a qualitative approach, whose main purpose is the development of a guide for journalistic coverage on HIV/AIDS in Brazil. This product is intended as a tool for the development of more responsible and humanized media content about people who are HIV positive. Stigma and discrimination are currently considered the main obstacles to accessing treatment and prevention measures; therefore, this research investigates how media representations of people living with HIV have been constructed over time, through the analysis of journalistic articles. Based on the understanding of the media as a social practice capable of producing meaning about reality, this work poses the following research question: In what ways can the media transform representations of people living with HIV? Among the methodologies chosen to achieve these objectives, documentary research was carried out, a questionnaire was applied to a group of 48 HIV-positive individuals, and interviews will also be conducted with journalists from institutions such as the Ministry of Health and the Joint United Nations Programme on HIV/AIDS (UNAIDS) to validate the proposed product. The guide, therefore, does not arise as a proposed solution to a historical problem, but rather as one of several initiatives focused on the representation of HIV-positive people and on combating stigma and discrimination.